Cooperation vs. firm-based innovation: A sectoral comparison in Portugal - Cesário, M. (2016)
In today's knowledge-intensive economies, the enterprises can have a strong economic and social influence as "market protagonists". Facing today's economic instability they ought to provide a constant stream of innovations to clients. Researchers suggest that firms can reshape the market through their innovations, for which can contribute some external expert knowledge. The process of developing an innovation may imply three types of approach: make; buy or cooperate with other agents to acquire specific competences or knowledge. This last occurs when the firms' internal knowledge or skill-base is not sufficient or effective and is conveniently complemented with external sources. Firms' cooperation, among them or with clients or other stakeholders, and its potential for innovation is not new. In this paper, our aim is to identify the sectors more willing to engage in cooperation initiatives in order to accomplish innovation. Thus, this paper is structured as follows: Introduction; 1. Literature Review (Innovation and its assets; Disclosing the process of innovation; Open innovation; Cooperation for innovation); 2. Research Design (The CIS instrument; Sampling); 3. Results (The nature of the innovation process by sector: cooperation-based vs. firm-based; The scale and scope of cooperation); Concluding Remarks. Using descriptive statistics, the first step will be to identify the sectors more willing to engage in cooperation initiatives in order to accomplish innovation. Secondly, for those sectors a more detailed analysis on the scale and scope of cooperation is developed. For this study a secondary dataset was used from the CIS-2012 (DGEEC, 2014). The CIS, operation acronym in the Eurostat for Community Innovation Survey, is the main statistical survey (mandatory for EU member states) on innovation in companies. The universe contemplates Portuguese companies with 10 or more employees belonging to the NACE codes. The INITIAL sample consisted of 9423 companies. 6840 valid answers were considered.